2011
DOI: 10.4155/tde.11.97
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Sensitizes Chemotherapeutic Drugs Via Modulation of PKC, telomerase, NF-κB and HDAC in Breast Cancer

Abstract: Background: Several tumor markers are overexpressed in breast cancer. Chemotherapy in breast cancer fails due to resistance to chemotherapeutic drugs. A phytochemical such as curcumin can be used in a therapeutic modality as it elicits anti-tumor effects. Methods: Action of curcumin on the expression of several tumor markers, such as protein kinase C, telomerase, NF-κB and histone deacetylase in MCF-7 (ER positive), MDA-MB-231 (ER negative), MCF-12F (control) and also in mice mammary tumors were investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Cytotoxic efficacy of cisplatin was determined by the MTT assay (Roy et al, 2011). Cells at a density of 104 were seeded in each of the 96 well plates and exponentially growing cells were treated with curcumin along with cisplatin of different concentrations (indicated in the Figure Legends) for 24 h. Cells treated with TSA (1 µM), a HDAC inhibitor along with cisplatin was considered as positive controls.…”
Section: Assessment Of Cytotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Cytotoxic efficacy of cisplatin was determined by the MTT assay (Roy et al, 2011). Cells at a density of 104 were seeded in each of the 96 well plates and exponentially growing cells were treated with curcumin along with cisplatin of different concentrations (indicated in the Figure Legends) for 24 h. Cells treated with TSA (1 µM), a HDAC inhibitor along with cisplatin was considered as positive controls.…”
Section: Assessment Of Cytotoxicitymentioning
confidence: 99%
“…Expressions of HDAC (1 and 2) using specific antibodies were determined in curcumin treated cells by western blot analysis and HDAC activity was measured using assay kit (Roy et al, 2011). Briefly, treated cells were harvested, washed in wash buffer pH 7.5 (HEPES.…”
Section: Expression Of Hdac (1 and 2) And Hdac Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, curcumin has also been identified as an inhibitor of RTKs. Curcumin inhibits EGF-stimulated tyrosine phosphorylation of EGFR [6,[70][71][72] and decreases the activation of down-stream signaling in cell lines [6,[70][71][72]. A recent report has indicated that curcumin exhibits its anti-tumor effect by regulating miRNAs and the expressions of their target genes [73].…”
Section: Cip1mentioning
confidence: 99%
“…Numerous studies have reported that curcumin can inhibit NF-κB pathway in various cancer cells, including breast, ovary, prostate, colorectum, and pancreas [65][66][67][68][69]. Curcumin also inhibits the expressions of COX-2 and cyclin D1 [70,71]. Moreover, curcumin has also been identified as an inhibitor of RTKs.…”
Section: Cip1mentioning
confidence: 99%